Viajeros: The Assessment of an Online Minibus Ticket Reservation System - Jerome P. Cabatit Jr; Mariya Donica Leinne B. Capia; Jan Lorenz P. Tubije; Sean Kent P. Hermoso; Cris Norman P. Olipas (International Journal of Integrative Sciences, 2023)
Transportation issues persist due to the pandemic, limited public transportation, and strict passenger capacity regulations. Traditional systems requiring physical visits to terminals for ticket purchases and fare payments pose difficulties for commuters. To address these challenges, the researchers developed the Viajeros web application, benefiting both the company and customers. Using a developmental research design, they assessed the system's technical aspects and quality with input from IT experts and end-users. Results revealed high satisfaction with the system's technical features and usability. The solution effectively resolved problems related to ticket and seat reservations for minibuses, improving transportation efficiency and convenience. Recommendations include incorporating an alternative payment option to accommodate smartphones without QR scanning capabilities and enhancing the user interface for better user experience. These findings can guide the development of similar reservation and management systems, benefiting future researchers and practitioners. Implementing these recommendations can advance the field, benefiting residents of Rizal, Nueva Ecija, and potentially influencing global systems